2021
DOI: 10.1155/2021/8827124
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on Effect of Nanomaterials on Workability and Mechanical Properties of High‐Performance Concrete

Abstract: The application of nanomaterials in high-performance concrete (HPC) has been extensively studied worldwide due to their large surface areas, small particle sizes, filling effects, and macroquantum tunneling effects. The addition of nanomaterials in HPC has great contribution to enhancing the pore size of the cementitious matrix, improving the hydration of cement, and making the matrix much denser. In order to present an exhaustive insight into the feasibility of HPC reinforced with nanomaterials, the new devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 105 publications
2
9
0
Order By: Relevance
“…The results of density of all mixes are presented in Table (5) and Figure (10). As expected, the NMk mix has a higher density than that of the control, NC, or NS mix.…”
Section: -2-1 Densitysupporting
confidence: 56%
See 1 more Smart Citation
“…The results of density of all mixes are presented in Table (5) and Figure (10). As expected, the NMk mix has a higher density than that of the control, NC, or NS mix.…”
Section: -2-1 Densitysupporting
confidence: 56%
“…They concluded that the incorporation of nano silica in cement paste and mortar with the right composition will improve their mechanical properties. The positive impacts of utilizing nano silica in concrete, cement paste and mortar have appeared in earlier publications [7][8][9][10]. Ghafarti et al [11] and Tawfik et al [12] achieved the best performance of concrete when using 3 wt.…”
Section: -Introductionmentioning
confidence: 92%
“…Modern industries such as textiles, automotive, civil engineering, construction, solar technologies, environmental applications, medicine, transportation agriculture, and food processing, among others are largely reaping the benefits of nano-scale computer chips and other devices. In simple terms, everything out there in nanoindustrial applications has something to do with computer-based applications in the nanoindustry [ 31 , 32 , 33 ]. Thus, all the applications discussed in this review more or less originate from nanocomputers.…”
Section: Nanotechnology Applicationsmentioning
confidence: 99%
“…Apart from cement formulations, nanoparticles are included in repair mortars and concrete with healing properties that help in crack recovery in buildings. Furthermore, nanostructures, titanium dioxide, zinc, and other metallic oxides are being employed for the production of photocatalytic products with antipathogenic, self-cleaning, and water- and germ-repellent built-in technologies [ 33 ]. Similarly, quantum dot technologies are progressively employed for solar energy generation (a concept discussed later).…”
Section: Nanotechnology Applicationsmentioning
confidence: 99%
“…The use of nano silica (NS) for supplementing cementing materials is a new technology that has been applied to concrete manufacturing to enhance the mechanical properties of hardened concrete [ 1 ]. In general, nanomaterials have been utilized in enhancing the performance of concrete due to their compacting microstructure influence and hastening the reaction of cement hydration [ 2 , 3 ]. Currently, NS has gained the attention of reinforced concrete (RC) investigators due to its significant enhancement of mechanical and chemical performance in RC structures.…”
Section: Introductionmentioning
confidence: 99%